Study in Changes of Physico-Chemical Parameters in Deolite C-20 Resin After &γ-treatment - Lokhande, R.S.; Prasad Surendran, Binu; S. Parbhavalkar, Tirtha (Asian Journal of Chemistry, 2012)
Ion-exchanger materials have been an integral part of the radiochemical process application and in clean-up operation of low level aqueous waste streams. They are widely used in various purposes including in nuclear power plants. Therefore an attempt is made to understand the effect of γ-treatment on the physico chemical parameters of the resin Deolite C-20.